The Implementation of Eradication of Mosquito Nest PSN 3M Plus Program in Jember Region - Mawaddah, Nurul; Rachmah, Siti; June , Mohammad Septyan Army (Al-Hijrah Indonesia, 2023)
Dengue Hemorrhagic Fever (DHF) is a viral infectious disease transmitted by mosquitoes and a public health problem worldwide. The implementation of the vector control program as an effort to prevent dengue through the Eradication of Mosquito Nest (PSN) 3M plus program in the community is still not optimal, due to a lack of community participation. The purpose of this study was to determine the effectiveness of the implementation of the PSN 3M Plus program in the Jember area. The research design used a pre-experimental design with one group pre-test and post-test design. The research sample was the people in the area who had been infected with DHF in the last 1 year at a distance of 100 meters from the sufferer, namely 50 families. The data collection technique used a community behavior questionnaire in implementing the 3M plus PSN program. Data analysis techniques were carried out using univariate and bivariate methods. The results of this study show that 40% of respondents experienced an increase in PSN behavior scores after implementing PSN 3M Plus, 44% experienced a decrease and 16% had a fixed score. Program implementation carried out through socialization efforts, the Movement 1 House 1 Jumantik (G1R1J) monitoring movement by jumantik cadres in less than 2 months was able to change the positive behavior of the community by 40%. It is hoped that the PSN 3M plus program will continue to be socialized and its implementation monitored so that the program's objectives are achieved as an effort to prevent DHF.